Trade overlap and trade pattern indices of intra-industry trade: Theoretical distinctions versus empirical similarities - Jacques Silber; Udo F. Broll (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
In a recent survey of intra-industry trade indices Kol and Mennes (1986) suggested to make a basic distinction between the study of matching trade flows and that of the similiarity oftrade patterns. The present paper shows that in both cases measures of intra-industry trade may be expressed either as distances or as equality indices, and derives the corresponding families of intra-industry indices. An empirical section indicates however that despite these theoretical distinctions, most of the intra-industry trade indices are highly correlated.
Keywords: 330